2014
DOI: 10.1080/02687038.2014.928665
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia blog talk: How does stroke and aphasia affect the carer and their relationship with the person with aphasia?

Abstract: Citation: Winkler, M., Bedford, V., Northcott, S. and Hilari, K. (2014). Aphasia blog talk:How does stroke and aphasia affect the carer and their relationship with the person with aphasia?. Aphasiology, doi: 10.1080Aphasiology, doi: 10. /02687038.2014 This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent AbstractBackground: Carers of stroke survivors with aphasia are at risk of experiencing negative bio-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 34 publications
1
48
0
1
Order By: Relevance
“…Further, other stroke studies have found that perceived functional support remains relatively stable across time post onset (King, ShadeZeldow, Carlson, Feldman, & Philip, 2002;Tsouna-Hadjis, Vemmos, Zakopoulos, & Stamatelopoulos, 2000). Thus despite the well-documented strains placed on intimate relationship following a stroke (Pallesen, 2014;Winkler, Bedford, Northcott, & Hilari, 2014) this construct may be relatively stable, which is the pattern found in the general population (Sarason et al, 1986). It has been hypothesised that perceived functional support may in fact reflect attachment style: high perceived support related to secure attachment; low perceived support related to anxious or avoidant attachment (Sarason et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Further, other stroke studies have found that perceived functional support remains relatively stable across time post onset (King, ShadeZeldow, Carlson, Feldman, & Philip, 2002;Tsouna-Hadjis, Vemmos, Zakopoulos, & Stamatelopoulos, 2000). Thus despite the well-documented strains placed on intimate relationship following a stroke (Pallesen, 2014;Winkler, Bedford, Northcott, & Hilari, 2014) this construct may be relatively stable, which is the pattern found in the general population (Sarason et al, 1986). It has been hypothesised that perceived functional support may in fact reflect attachment style: high perceived support related to secure attachment; low perceived support related to anxious or avoidant attachment (Sarason et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The social consequences of aphasia can also be severe. The family unit is placed under strain [4,5]; people take part in fewer social activities [6], and are at risk of losing contact with friends and their wider social network [7,8]. Neglecting psychosocial well-being potentially has broader ramifications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the contextual factors impacting on social participation were investigated. 29 . PWA experienced a higher degree of dependence and changes in the roles they played 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In two studies with moderate and high levels of evidence respectively, the Social Integration subscale of the CIQ was used 20,21 , which indicated reduced social integration in working-age PWA, with a decrease in time spent on leisure activities 20 . The remaining two studies on moderate and low levels of evidence respectively, used the ICF to report on their findings 24,29 . Of the aspects investigated, restrictions in recreation and leisure activities were noted.…”
Section: Education and Employmentmentioning
confidence: 99%
See 1 more Smart Citation